PERLINDUNGAN HUKUM BAGI KONSUMEN AIR MINUM ATAS LAYANAN PDAM TIRTA SIAK KOTA PEKANBARU DITINJAU DARI UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Titus Alam Sinaga; Maryati Bachtiar; Dasrol ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Among the complaints of the customers are the taps until the water quality is very bad home-home even unfit for consumption as drinking water or for cooking. We each month to pay the bills that do not fit with the water that we use. We hold water and be spilled and dumped because the water is dirty, smelly and sometimes the smell of garbage. From the first, as this issue continues to be present when talking about PDAM Pekanbaru. Customers upset because they feel disadvantaged by poor water quality especially when it rains. But, until now there is no fix for this problem. Even changing penguasapun in Pekanbaru not bring good changes to the quality of service to consumers.This study using sociological juridical approach. Sociological juridical research or empirical research approach is to look at in terms of the fact that occur in the field. While the descriptive nature of the research is aimed at providing a clear picture of the issues examined. Population and sample in this study is a population study in PDAM Tirta Siak Pekanbaru City and sample the Director of PDAM Tirta Siak Pekanbaru and Consumer Services Drinking Water Using Tirta Siak Pekanbaru in Pekanbaru District of the City.The results of this study are: First, the law for the protection of drinking water consumers for services PDAM Tirta Siak Pekanbaru city on water quality is very bad, resulting in non-fulfillment of the rights of consumers, resulting in harm to consumers both Financial and nonfinancial. Second, the recognition of the people who use the water utility PDAM TirtaSiak Pekanbaru, the absence of realized what strived by PDAM TirtaSiak Pekanbaru City until recently, even the water quality is getting worse. If rainy days, the water supplied by PDAM Tirta Siak Pekanbaru City unfit for dikosumsi. Legal efforts are made to consumers who are disadvantaged on layanana drinking water by PDAM Tirta Siak Pekanbaru City may file a lawsuit to the Consumer Dispute Settlement Board (BPSK) which is based on Law No. 8 of 1999 on Consumer Protection.Keywords: Implementation - Legal - Drinking Water For Consumer - consumer protection